Spin-gapless semiconducting Cl-intercalated phosphorene bilayer: a perfect candidate material to identify its ferroelectric states by spin-Seebeck currents. Issue 8 (31st January 2022) - Wu, Dan-Dan; Ji, Yu-Tian; Du, Gui-Fang; Yue, Xiao-Yu; Wang, Yi-Yan; Li, Qiu-Ju; Sun, Xue-Feng; Fu, Hua-Hua
Abstract : Two-dimensional multiferroic materials, combining the ferroelectric (FE) state with the ferromagnetic (FM) state, have long been regarded as one of the core topics in materials science. Abstract : Two-dimensional multiferroic materials, combining the ferroelectric (FE) state with the ferromagnetic (FM) state, have long been regarded as one of the core topics in materials science. However, realizing a low-energy-dissipation approach to read the FE states is still a hard task. Here, we propose a bilayer phosphorene halogenated by chlorine (Cl) adatoms to induce the layer-dependent single-atom FE states with vertical electric polarization and construct the related spin caloritronic devices. Our theoretical studies uncover several interesting findings: (i) the halogenated monolayer phosphorene produces single-atom FE states and two nearly symmetrical spin-splitting states around the Fermi level, providing two spin-dependent transport channels for the generation of a well-defined spin-Seebeck effect (SSE); (ii) a pure thermal spin current can be obtained by adjusting the Cl-adatom concentration or by using an in-plane strain engineering technique; (iii) the spin-Seebeck current is tightly associated with the layer-dependent FE state, and they both can be switched simultaneously to the other layer by an external electric field. Our theoretical results not only propose a low-energy-dissipation approach to realize the readout of single-atom FE states, but also develop further the new interdisciplinary subject, i.e., the spin-ferroelectro-caloritronics.